Current conduction mechanism of MIS devices using multidimensional minimization system program. Issue 7 (June 2015) - Rouag, N.; Ouennoughi, Z.; Rommel, M.; Murakami, K.; Frey, L.
Abstract: The present work presents an evaluation approach which enables the in-depth analysis of current–voltage ( I – V ) characteristics of MIS devices to determine their current transport mechanisms using a multidimensional minimization system program. Exemplarily, the current transport mechanisms were determined for a TiN/SiO2 /p-Si MOS and a TaN/HfSiO/SiO2 /p-Si MIS structure by fitting the analytical expressions for different current transport mechanisms to experimental I – V data in a wide range of applied biases and temperatures. The considered mechanisms for the investigated samples include temperature dependent Fowler–Nordheim (FN) tunneling and Poole–Frenkel (PF) emission as well as ohmic conduction. The presented approach can easily be extended to account for additional mechanisms such as trap assisted tunneling (TAT) if relevant for different samples. In contrast to typical extraction procedures which determine current conduction mechanism parameters sequentially, in this work, the adjustable fit parameters are extracted in a single operation using the Levenberg–Marquardt algorithm (Nash, 1990) to obtain a least-square fit of the model to measured I – V characteristics. Thus, simultaneously occurring current mechanisms can properly be evaluated which allows to determine the fraction of each conduction mechanism quantitatively for each voltage.